ABOUT A NEW ARTISTIC STYLISTIC DEVICE - Saidmurad Kholbekov (Journals Park Publishing, 2024)
This article examines the new visual arts.
Keywords: palindrome, maqlubi mustavi, stylistic devices, alliteration, tavze, tashbeh, repetition of sound, new stylistic device.